E47 modulates hepatic glucocorticoid action - M. Charlotte Hemmer (Nature Portfolio, 2019)
Glucocorticoids (GCs) are widely used anti-inflammatory drugs; however, long-term treatment causes metabolic side effects. Here, the authors show that E47 is a modulator of glucocorticoid receptor activity for a subset of target genes in mouse liver, and that loss of E47 protects mice from hyperglycemia and hepatic steatosis in response to GCs.